Relaxation of the entanglement spectrum in quench dynamics of topological systems. (18th July 2017) - Jhu, Yi-Hao; Chen, Pochung; Chung, Ming-Chiang
Abstract: In this paper, we investigate how the entanglement spectrum relaxes to its steady-state values in one-dimensional quadratic systems after a quantum quench. In particular, we apply saddle-point expansion to dimerized chains and 1D p -wave superconductors. We found the entanglement spectrum to always exhibit a power-law relaxation superimposed with oscillations at certain characteristic angular frequencies. For dimerized chains, we found the exponent ν of the power-law decay to always be 3 / 2 . For 1D p -wave superconductors, however, we found that, depending on the initial and final Hamiltonian, the exponent ν can take its value from a limited list of values, the smallest possible of which is ν = 1 / 2, which leads to a very slow convergence to its steady-state value.